Development of a family-centred core outcome set for infants with developmental dysplasia of the hip treated with a brace - Joanna Craven; Olivia O’Malley; Daniel C. Perry (Bone & Joint Open)
Aims: This study aims to define a set of family-centred core outcomes for infants undergoing brace treatment to facilitate consistent reporting for future high-quality research. Methods: Family-centred outcomes will be identified through a literature review and a scoping survey involving key stakeholders, including parents, healthcare professionals, and researchers. These outcomes will then be rated for their perceived importance in a two-stage modified Delphi process with the same stakeholders. Finally, a consensus meeting will be held to establish the final core outcome set (COS). Conclusion: The impact of brace treatment on the family is profound, but seldom considered in randomized controlled trials. This COS can independently standardize reporting on the family’s experience, and potentially become part of a broader COS for developmental dysplasia of the hip in infants undergoing brace treatment. Cite this article: Bone Jt Open 2024;6(1):21–25.